Gevrey Problem for a Mixed Parabolic Equation with a Singular Coefficient - Mamanazarov, A. O. (Journal of mathematical sciences (New York, N.Y.), 2021)
In this paper, we examine the unique solvability of the Gevrey problem for a mixed parabolic equation with singular coefficients in a band. We prove the existence and uniqueness of a solution to the problem stated. The uniqueness of a solution is proved by the method of energy integrals and the existence by methods of the theory of Volterra, Fredholm, and singular integral equations.